The determination of infrared optical constants of rare earth fluorides by classical Lorentz oscillator model - Su, Wei-tao; Li, Bin; Liu, Ding-quan; Zhang, Feng-shan (Journal of physics. D, Applied physics, 2007)
Rare earth fluoride (REF3, RE = La, Ce, Pr, Sm, Er, Yb, Y) films were deposited on Ge(1 1 1) and silicon wafers in order to determine optical constants from the near infrared up to the high frequency tail of the reststrahlen band. The FT-IR transmission spectrum and the reflection spectrum were used to examine the infrared optical properties of the fluorides. The optical constants of the films in the infrared spectrum from 2 to 20 mum were calculated using the classical Lorentz oscillator model by fitting the transmission spectrum. The reflective spectrum of the fluorides on silicon was used to demonstrate the absorption difference in this region. It is found that the extinction coefficients of rare earth fluorides films with Pnma structure (REF3, RE = Y, Yb, Er) are larger than the other fluorides films with structure (REF3, RE = La, Ce, Pr, Sm) from 15 to 20 mum.